2010
DOI: 10.1002/app.31025
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly(ethylene glycol) by electrolysis during the Cu electroplating: A combined experimental and density functional theory study

Abstract: The polymer additives are key factor materials in the Cu electroplating process, essential for controlled acceleration and inhibition of Cu deposition. In this study, the degradation behavior of a polymer additivepoly(ethylene glycol) (PEG)-during the Cu electroplating was investigated by MALDI-TOF MS technique. The PEG was completely degraded after 4 h at a constant electric current density of 13 mA/cm 2 , whereas it showed no degradation without an electric field even at a very low pH (pH < 1). The pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Kelly et al reported that the additive poly(ethylene glycol) (PEG) inhibits Cu electrodeposition by adsorption onto the surface of the electrodes. [6][7][8][9] Yokoi et al reported that, in the presence of Cl À , PEG forms a physical diffusion barrier that suppresses electrodeposition. 10,11) Landau et al reported several polyether compounds that exhibit a stronger inhibition effect compared with PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al reported that the additive poly(ethylene glycol) (PEG) inhibits Cu electrodeposition by adsorption onto the surface of the electrodes. [6][7][8][9] Yokoi et al reported that, in the presence of Cl À , PEG forms a physical diffusion barrier that suppresses electrodeposition. 10,11) Landau et al reported several polyether compounds that exhibit a stronger inhibition effect compared with PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al reported that poly(ethylene glycol) (PEG) inhibited copper electrodeposition by adsorption to the surface of the electrodes. [6][7][8][9] Landau et al reported several polyether compounds that exhibited a stronger inhibition effect compared with PEG. 10) Moffat et al investigated the rate of displacement of the blocking PEG layer by bis(3sulfopropyl)-disulfide (SPS) adsorption.…”
mentioning
confidence: 99%
“…In another example, Takeda et al76, 269, 270 analyzed the ultrasonic degradation of PMMA and other synthetic polymers using MALDI‐TOF, and Gunes et al187 examined the ultrasonic degradation of PET/PEN blends. Dannoux et al169, 246 used ESI‐MS to study the degradation of poly(ether‐urethane) under irradiation and Won et al studied the degradation of poly(ethylene glycol) during a Cu electroplating process 271. Wagner et al272 used TOF‐SIMS to study the degradation of random copolymers of MMA and EGDMA under 5keV SF5 + ion bombardment.…”
Section: Environmental Polymer Degradationmentioning
confidence: 99%